Development of an oat database - Bräutigam, Marcus; Jonsson, Anders; Olsson, Björn; Olsson, Olof (MTT, 2004)
We have recently built a new database that contains information about oat gene sequences, gene expression profiles, protein structure and activities and primers for cloning and mapping purposes. The database is the property of AvenaGene AB and is denoted AGOD for AvenaGene Oat Database. It is accessible at http://www.agod.org. The database was built using PostgreSQL, which is an object-relational database management system. It is combined with a web-based user-friendly interface developed with the PHP scripting language. There is also a webbased BLAST engine connected to the database, which gives the user the opportunity to search AGOD with own sequence data. Our long-term aim is to make AGOD the primary repository for information about oat-related issues and the major part of AGOD will therefore be made publicly available. At present, this database contains more than 10,000 EST sequence entries, full-length cDNA sequences and information about deduced protein activities. OatDB will be continuously updated with new sequence data, as well as with new results derived from various biological experiments, advanced bioinformatics analysis, various protocols, literature references and oat-related web links.
Keywords: Ka; oat data base; EST sequence